2011
DOI: 10.1158/0008-5472.can-11-1295
|View full text |Cite
|
Sign up to set email alerts
|

A Kinome-Wide Screen Identifies the Insulin/IGF-I Receptor Pathway as a Mechanism of Escape from Hormone Dependence in Breast Cancer

Abstract: Estrogen receptor α (ER)-positive breast cancers adapt to hormone deprivation and become resistant to antiestrogens. In this study, we sought to identify kinases essential for growth of ER+ breast cancer cells resistant to long term estrogen deprivation (LTED). A kinome-wide siRNA screen showed that the insulin receptor (InsR) is required for growth of MCF7/LTED cells. Knockdown of InsR and/or insulin-like growth factor-1 receptor (IGF-1R) inhibited growth of 3/4 LTED cell lines. Inhibition of InsR and IGF-1R … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 46 publications
5
110
0
Order By: Relevance
“…IGF, insulin-like growth factor; c/c, case-control study; ELISA, enzyme-linked immunosorbent assay; BMI, body mass index; HRT, hormone replacement therapy; OCont, oral contraceptive; IRMA, immunoradiometric assay; NR, not reported. study (20) reported that exogenous hormone use may affect the peptide levels in the IGF signaling pathway, which induced the decrease of circulating IGF-1 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…IGF, insulin-like growth factor; c/c, case-control study; ELISA, enzyme-linked immunosorbent assay; BMI, body mass index; HRT, hormone replacement therapy; OCont, oral contraceptive; IRMA, immunoradiometric assay; NR, not reported. study (20) reported that exogenous hormone use may affect the peptide levels in the IGF signaling pathway, which induced the decrease of circulating IGF-1 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 S6K1 is also one of the kinases required for hormoneindependent breast cancer cell proliferation. 48 In addition, mTORC1 serves as an important signaling node for several growth factor signaling pathways that are implicated in endocrine resistance, such as MAPK and PI3K. Thus, mTORC1 hyperactivation by converging stimuli would be targeted by the addition of mTOR inhibitors to endocrine therapy.…”
Section: S6k1 In Er-positivementioning
confidence: 99%
“…P-S6K1 and P-S6 positively correlated with high proliferative index in letrozole-treated patients, indicative of endocrine resistance and poor patient outcome. 48 Since a significant number of patients carry S6K1 amplification and exhibit S6K1 overexpression or overexpression, S6K1 could be utilized as a prognostic marker. Detection of S6K1 expression in breast cancer could be an effective way to target and treat patients most likely to respond to the combination of mTORC1 and endocrine inhibitors.…”
Section: S6k1 In Er-positivementioning
confidence: 99%
See 2 more Smart Citations